Penggunaan Kromium Organik dari Beberapa Jenis Fungi terhadap Aktivitas Fermentasi Rumen Secara in Vitro - W D Astuti; T Sutardi; D Evvyernie; T Toharmat (Media Peternakan, 2006)
Chromium appears to be an essential trace element since 1959, but its effect on ruminal microbes is not clear yet. This experiment was conducted to study the effects of organic chromium supplementation on rumen fermentation activity. An in vitro technique was held using randomized block design with 13 treatments and 3 replications. There were four kinds of organic Cr used, produced with four different species of fungi as carriers. Fungi used as carriers were Saccharomyces cerevisiae, Aspergillus oryzae, Rhizophus oryzae and "ragi tape". The result indicated that the optimum organic Cr supplementation was 1 mg organic Cr/kg dry matter. Supplementation of 1 mg organic Cr/kg dry matter increased dry matter and organic matter digestibilities. It also tended to increase NH3 and total VFA production. Propionate production increased, which decreased methane production and increased hexose conversion efficiency in several treatments. Each fungus used as carrier of organic Cr resulted in different effects on rumen fermentation activity, but the effects was within a normal range. It was concluded that either Saccharomyces cerevisiae, Aspergillus oryzae, Rhizophus oryzae or "ragi tape" could be used as carrier in organic Cr production. Key words : organic Cr, ruminal microbes, Saccharomyces cerevisiae, Aspergillus oryzae, Rhizophus oryzae, "ragi tape"